Dynamics of Air Pollution and its Dispersion in a Topographically Constrained Urban Area: A Case Study of Kathmandu Valley (Pokhara Engineering College Journal, 2026)
Kathmandu, one of the world’s prominent cultural and touristic cities, has undergone rapid urbanization over recent decades, creating substantial challenges for environmental quality management amid accelerating population growth and infrastructure development. This study examines the meteorological characteristics, ambient air quality, and pollutant dispersion mechanisms in the Kathmandu Valley through an integrated analysis of primary observations, secondary datasets, and numerical simulations. Meteorological and air quality data from multiple monitoring stations indicate strong seasonal variability, with daily mean temperatures ranging from approximately 10 °C to 24 °C. Higher wind speeds (~6 m/s) prevail in spring and summer, while calm winds dominate autumn and winter, accounting for more than 50% of observations. Particulate matter concentrations frequently exceed guideline levels, with PM10 surpassing 100 μg/m³ and PM2.5 reaching up to 80 μg/m³, particularly during winter, when pollution levels are more than twice those observed in spring and autumn. Monsoonal rainfall significantly suppresses particulate concentrations during summer. Source characterization highlights the predominance of soil-based dust, which accounts for over 60% of non-ionic components and approximately 25% of PM10, alongside a relatively high black carbon fraction (~17%). Numerical simulations reveal a pronounced diurnal mountain–valley breeze system, with mountain breezes dominating at night and valley breezes prevailing during the day. Stronger north–south airflow governs pollutant transport, causing emissions from the northern and central Valley to disperse widely, while pollutants originating from southern and southeastern sources exhibit limited penetration into the urban core.